A cross-sectional study of bovine brucellosis and test performance in intra-and peri-urban production systems in and around Addis Ababa, Ethiopia - Asfaw, Y.; Molla, B.; Zessin, K.H.; Tegegne, Azage (1998)
A cross-sectional study of bovine brucellosis was carried out from May to October 1997 on 42 dairy farms located in Addis Ababa, Sebeta, Kaliti and Debre Zeit, Ethiopia. An overall herd infection rate of 33.3 percent was established. With respect to the production systems, 100 percent, 30 percent and 12.5 percent of the farms were infected in peri-urban, intra-urban secondary town and inter-urban systems, respectively. In individual animals, the overall prevalence rate was 8.1 percent. Highest prevalence rate of 9.8 percent was observed in the age group 2 to 4 years. Infection rates of 9.1 percent and 3.3 percent was observed in farms that keep more than 100, and less than 50 animals, respectively. The infection rates were significantly different between the age group < or = 2 years and >2 years (p<0.05). An odds ratio (OR) of 2.14 (CI: 1.04-4.83) between age and Brucella infection, and 2.99 (CI: 1.29-8.06) between herd size and Brucella infection were determined. Agreement (kappa values) between RBPT+/CFT+ and MRT tests was 0.31 (first MRT), 0.43 (first and second MRT results pooled) and 0.58 (first, second and third MRT results pooled). Good agreement (k = 0.74) was found between RBPT+ and RBPT+/CFT+ serial testing procedure. The sensitivity and specificity of MRT were 57.1 percent and 89.3 percent, and RBPT 100 percent and 94.6 percent, respectively. An OR of 15.58 (CI: 1.72-79.16) was calculated for the association between abortions and Brucella infection.